The Effect Of Competitor Advertising And Product Quality On Brand Switching Of Smartphone Users On Borju Cell Counter, Kaur District - Medi Oktafianus; Neri Susanti; Mimi Kurnia Ningsih (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the effect of competitor advertisements and product quality on brand switching of smartphone users at the Kaur Regency Cell Borju Cell Counter. The sample in this study was 92 consumers who moved the smartphone brand to the Kaur Regency Borju Cell Counter. Data collection using a questionnaire and the method of analysis used is multiple linear regression, test of determination and hypothesis testing. The results of regression analysis show Y = 8.363 + 0.310X1 + 0.502 X2 + e. This illustrates a positive direction of regression, meaning that there is a positive influence between X1 (competitor advertisement) and X2 (product quality) on brand shift (Y). The coefficient of determination of the Adjust R square is 0.483. This means that X1 (competitor advertisement), X2 (product quality), has a contribution to brand shift (Y) by 48.3% while the remaining 51.7% is influenced by other variables not examined in this study. Competitor advertisements have a positive and significant effect on brand switching on customers of the Kaur Regency Borju Cell Counter. This illustrates that the increasing number of competitor's advertisements will increase the occurrence of brand switching. Product quality shows a positive and significant effect on brand switching on customers of the Kaur Regency Borju Cell Counter. This illustrates that the increasing quality of the product will increase the occurrence of brand switching. Based on the results of simultaneous hypothesis testing, it can be seen that together competitor advertisements and product quality have a positive and significant effect on brand switching on customers of Kaur Regency Bourge Cell Counter.